Pengaruh Persepsi Kemudahan dan Persepsi Risiko terhadap Minat Menggunakan SPayLater - Abdul Holik; Asep Maulana (Universitas Batanghari, 2023)
The study aims to find out, explain, and analyze and test the Effect of Perceived Ease of Use and Perceived Risk on Interest in using the SPayLater. This research was conducted using quantitative methods with descriptive and verification approaches, by collecting presentations, through the analys process and hypothesis testing as well as making conclusions and suggestions from the research results. The sample used is simple random sampling method, the number of sampels is obtained by using the formula of Isaac and Michael with an error rate of 10%, obtained 270 samples from 87.277 populations. The results of this study showed that there is correlation between Perceived Ease of Use and Perceived Risk which was 0,484 with a quite strong correlation value. The partial effect of Perceived Ease of Use on Interest in Using is equal 52,9% which means that Perceived Ease of Use has a positive effect on Interest in Using SPayLater. The partial effect of Perceived Risk on Interest in Using is equal 29,7% which means that Perceived Risk has a positive effect on Interest in Using SPayLater. The simultaneous of Perceived Ease of Use and Perceived Risk on Interest In Using of 52% this show that Perceived Ease of Use and Perceived Risk have a contribution to Interest in Using of 52% and the remaining 42% is a contribution from other variables not examined.